An additively manufactured γ-based high Nb-TiAl composite via coherent interface regulation. (15th January 2023) - Xue, Hui; Liang, Yongfeng; Peng, Hui; Wang, Yanli; Shang, Shun-Li; Liu, Zi-Kui; Lin, Junpin
Abstract: Novel γ-based TiAl alloys are a promising alternative to conventional dual-phase TiAl alloys, which suffer from microstructural degradation and solid-state phase transformations at high temperatures. However, monolithic intermetallic γ phases exhibit poor plasticity, and they are incompatible with conventional manufacturing techniques. In this study, a microstructural modification was used to enable the preparation of a single-phase matrix from an Nb-rich TiAl metal matrix composite using additive manufacturing (AM) techniques. Micro/nano-precipitates of Ti5 Si3 and Ti2 AlN were produced by adding Si3 N4 precursors to the pre-alloy powder, which reacted with the γ-TiAl matrix during the AM process. Thus, strong interfacial cohesion was achieved. The Ti5 Si3 and Ti2 AlN precipitates refined the grains in the metal and Ti5 Si3 strengthened the grain boundaries. The enhanced interfacial cohesion and unique distribution of precipitates suppressed intergranular cracks during AM and increased the plasticity of the alloy. Graphical Abstract: Image, graphical abstract